Enslaved African Women in Nineteenth-Century Iran: The Life of Fezzeh Khanom of Shiraz - Lee, Anthony A. (Iranian studies, 2012)
Fezzeh Khanom (c. 1835-82), an African woman, was a slave of Sayyed 'Ali-Mohammad of Shiraz, the Bab. Information about her life can be recovered from various pious Baha'i histories. She was honored, and even venerated by Babis, though she remained subordinate and invisible. The paper makes the encouraging discovery that a history of African slavery in Iran is possible, even at the level of individual biographies. Scholars estimate that between one and two million slaves were exported from Africa to the Indian Ocean trade in the nineteenth century, most to Iranian ports. Some two-thirds of African slaves brought to Iran were women intended as household servants and concubines. An examination of Fezzeh Khanom's life can begin to fill the gaps in our knowledge of enslaved women in Iran. The paper discusses African influences on Iranian culture, especially in wealthy households and in the royal court. The limited value of Western legal distinctions between slavery and freedom when applied to the Muslim world is noted.